2018
DOI: 10.1371/journal.pone.0191728
|View full text |Cite
|
Sign up to set email alerts
|

The influence of political ideology and trust on willingness to vaccinate

Abstract: In light of the increasing refusal of some parents to vaccinate children, public health strategies have focused on increasing knowledge and awareness based on a “knowledge-deficit” approach. However, decisions about vaccination are based on more than mere knowledge of risks, costs, and benefits. Individual decision making about vaccinating involves many other factors including those related to emotion, culture, religion, and socio-political context. In this paper, we use a nationally representative internet su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
216
4
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 274 publications
(251 citation statements)
references
References 44 publications
(25 reference statements)
22
216
4
9
Order By: Relevance
“…This finding is consistent with research by the Pew Research Center (2017c), which found that liberals tend to place more trust in science magazines than moderates and conservatives and were also less likely to assert that scientists overstate their research findings' implications. This finding is also consistent with a broader trend toward distrust in various forms of expertise, particularly among conservatives (Baumgaertner, Carlisle, & Justwan, 2018). Thus, this paper helps to reinforce the finding that trust is eroding in experts, particularly among conservatives but also among moderates (or, from another perspective, is perhaps remaining irrationally high among liberals).…”
Section: Discussionsupporting
confidence: 83%
“…This finding is consistent with research by the Pew Research Center (2017c), which found that liberals tend to place more trust in science magazines than moderates and conservatives and were also less likely to assert that scientists overstate their research findings' implications. This finding is also consistent with a broader trend toward distrust in various forms of expertise, particularly among conservatives (Baumgaertner, Carlisle, & Justwan, 2018). Thus, this paper helps to reinforce the finding that trust is eroding in experts, particularly among conservatives but also among moderates (or, from another perspective, is perhaps remaining irrationally high among liberals).…”
Section: Discussionsupporting
confidence: 83%
“…Decisions for vaccination, whether human or livestock, can often be more associated with religious and spiritual reasons, personal opinions, safety worries and additional information, beyond any knowledge of risks, costs, and benefits (10,11).…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%
“…As recipients of taxpayer funds, scientists are obligated to convey their research findings to the public in a way that communicates the value of basic research and within a framework where the public are stakeholders in this new knowledge. This is even more important in current times, where public opinion can be contrary to scientific evidence, such as climate change (Leiserowitz et al, 2013), childhood vaccinations (Baumgaertner et al, 2018) and genetically modified foods (Malyska et al, 2016). Programs that broaden the impact of research are required of some funding agencies, like the National Science Foundation in the USA.…”
Section: Perils and Pitfalls In Linking Genotype To Behavioral Phenotmentioning
confidence: 99%